2017
DOI: 10.1111/epi.13978
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of KCNQ channel activation in 2 potassium channelopathy mouse models of epilepsy

Abstract: This study shows that treatment strategies in channelopathy may have unexpected outcomes and that effective rebalancing of channel defects requires improved understanding of channel interactions at the circuit and tissue levels. The efficacy of KCNQ channel activation and manifestation of adverse effects were greatly affected by genetic background, potentially limiting KCNQ modulation as a way to prevent neurocardiac dysfunction in epilepsy and thereby SUDEP risk. Our data also uncover a potential role for KCN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The results obtained revealed that injection of either Lv-shGAS5 or Lv-miR-135a-5p significantly prolonged the epileptic latency and reduced the frequency of seizures. Although the implications of KCNQ3 and potassium channels in the pathogenesis of epilepsy have been illustrated in many studies, [35][36][37] the antiepileptic drugs dealing with potassium channels are still under investigated. This study highlighted a novel molecule mechanism that Lv-miR-135a-5p and Lv-shGAS5 are able to inhibit KCNQ3 expression in the rat models of epileptic seizure (Figure 4), indicating that downregulation of lncRNA GAS5 can decrease KCNQ3 through sponging miR-135a-5p to prolong latent period and to reduce seizure frequency.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained revealed that injection of either Lv-shGAS5 or Lv-miR-135a-5p significantly prolonged the epileptic latency and reduced the frequency of seizures. Although the implications of KCNQ3 and potassium channels in the pathogenesis of epilepsy have been illustrated in many studies, [35][36][37] the antiepileptic drugs dealing with potassium channels are still under investigated. This study highlighted a novel molecule mechanism that Lv-miR-135a-5p and Lv-shGAS5 are able to inhibit KCNQ3 expression in the rat models of epileptic seizure (Figure 4), indicating that downregulation of lncRNA GAS5 can decrease KCNQ3 through sponging miR-135a-5p to prolong latent period and to reduce seizure frequency.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced activity of these voltage-gated K + channels can generate the macroscopic M-type K + current ( I K(M) ), which is biophysically manifested by current activation in response to low-threshold voltage and, once activated, the current displays a slowly activating and deactivating property [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Targeting I K(M) is noticeably viewed as an adjunctive regimen for the management of various neurological or endocrine disorders associated with neuronal over-excitability, which include cognitive dysfunction, neuropathic pain, and epilepsy [ 27 , 28 , 29 , 30 ]. Alternatively, previous studies have demonstrated that KYNA-mediated vasodilation and hypotension could be attributed to the activation of KCNQ channels [ 18 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Once being activated, this type of K + currents can be sensitiv block by linopirdine and it is demonstrated to exhibit a slowly activating and deactiva property [46][47][48][49][50][51]. Alternatively, targeting IK(M) has been noticeably viewed as an adju tive regimen for the management of various neurological, smooth muscle, or endoc disorders closely linked to membrane hyperexcitability, which include cognitive dysfu tion, epilepsy, and over-active bladder [47,[52][53][54][55]. However, to our knowledge, how whether this agent can interact directly with KV channels to modify the amplitude gating of voltage-gated K + currents (e.g., M-type K + current) remain largely unknown Therefore, in terms of the considerations stated above, in the current study, we cided to explore the possible perturbations of SOL on IK(M) in pituitary GH3 cells mouse mHippoE-14 hippocampal neurons.…”
Section: Introductionmentioning
confidence: 99%